2019
DOI: 10.1096/fj.201902629r
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal inflammation suppresses blood Th1 polarization and gene clusters related to cellular energy metabolism in preterm newborns

Abstract: Chorioamnionitis (CA, fetal membrane inflammation) predisposes to preterm birth and is associated with increased neonatal infection risk, but the separate effects of prematurity, CA, and postnatal adaptations on this risk are unclear. Using pigs as models for infants, we examined the systemic immune‐metabolic status in cesarean‐delivered preterm pigs, with and without CA induced by intra‐amniotic (IA) LPS exposure. At birth, cord blood of preterm pigs showed neutropenia and low expressions of innate and adapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Numerous animal models of infection and sepsis have been established e.g., cecal ligation and puncture (23) and oral (24,25) or systemic bacterial challenge (26), but no rodent models can address the contributing effects of PN. The preterm pig is a unique model because it allows PN administration via umbilical catheter (27) and has multiple organ immaturities and infection susceptibility (26,(28)(29)(30), as found in preterm infants. Furthermore, systemic S. epidermidis administration to newborn preterm pigs can induce clinical and cellular responses (e.g., fever, inflammation, blood platelet and leukocyte depletion) that may progress to septic shock (acidemia and hypotension) 12-24 hours after infection, similar to sepsis caused by CONS and other bacteria in preterm infants (26).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous animal models of infection and sepsis have been established e.g., cecal ligation and puncture (23) and oral (24,25) or systemic bacterial challenge (26), but no rodent models can address the contributing effects of PN. The preterm pig is a unique model because it allows PN administration via umbilical catheter (27) and has multiple organ immaturities and infection susceptibility (26,(28)(29)(30), as found in preterm infants. Furthermore, systemic S. epidermidis administration to newborn preterm pigs can induce clinical and cellular responses (e.g., fever, inflammation, blood platelet and leukocyte depletion) that may progress to septic shock (acidemia and hypotension) 12-24 hours after infection, similar to sepsis caused by CONS and other bacteria in preterm infants (26).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, any postnatal gut influence of fetal inflammation appeared overshadowed by the immune-modulating effects of enteral feeding and microbial colonization just after birth. On the other hand, Muk et al showed that kidneys, in contrast to gut, lungs and liver (30), showed more robust and longer-term inflammatory reactions after prenatal Gram-negative infection in preterm pigs, confirming the postnatal systemic immune suppression assessed by blood transcriptome analyses (32). It remains that the immune effects of fetal inflammation are highly species-, time-, age-, pathogen-and organ-specific.…”
Section: Fetal Insults Affecting Newborn Immune Developmentmentioning
confidence: 91%
“…In an in vitro experiment, the frequency of Treg cells in stimulated blood was analyzed as previously described(28). In brief, blood after bacterial stimulation was lyzed to remove erythrocytes, washed with PBS, permeabilized (permabilization buffer, Thermofisher), blocked with porcine serum (Thermofisher Scientific), and stained with a mixture of FITC-conjugated mouse-IgG2b anti-porcine CD4 antibody (clone MIL17), APC-conjugated rat-IgG2a anti-porcine Foxp3 antibody (clone FJK-16s), and analyzed by a BD Accuri C6 flow cytometer (BD Biosciences, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Whole blood RNA of selected samples from in vitro and in vivo experiments was analyzed by whole transcriptome shotgun sequencing, as previously described(28), to profile immunometabolic pathways affected by relevant interventions. Briefly, RNA-seq libraries were constructed using 1000 ng RNA and VAHTS mRNA-seq V3 Library Prep Kit for Illumina (Vazyme, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation